Cisplatin Induces Cytotoxicity through the Mitogen-Activated Protein Kinase Pathways and Activating Transcription Factor 3 - St. Germain, Carly (Neoplasia Press Inc., 2010)
The mechanisms underlying the proapoptotic effect of the chemotherapeutic agent, cisplatin, are largely undefined. Understanding the mechanisms regulating cisplatin cytotoxicity may uncover strategies to enhance the efficacy of this important therapeutic agent. This study evaluates the role of activating transcription factor 3 (ATF3) as a mediator of cisplatin-induced cytotoxicity. Cytotoxic doses of cisplatin and carboplatin treatments consistently induced ATF3 expression in five tumor-derived cell lines. Characterization of this induction revealed a p53, BRCA1, and integrated stress response-independent mechanism, all previously implicated in stress-mediated ATF3 induction. Analysis of mitogen-activated protein kinase (MAPK) pathway involvement in ATF3 induction by cisplatin revealed a MAPK-dependent mechanism. Cisplatin treatment combined with specific inhibitors to each MAPK pathway (c-Jun N-terminal kinase, extracellular signal-regulated kinase, and p38) resulted in decreased ATF3 induction at the protein level. MAPK pathway inhibition led to decreased ATF3 messenger RNA expression and reduced cytotoxic effects of cisplatin as measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell viability assay. In A549 lung carcinoma cells, targeting ATF3 with specific small hairpin RNA also attenuated the cytotoxic effects of cisplatin. Similarly, ATF3-/- murine embryonic fibroblasts (MEFs) were shown to be less sensitive to cisplatin-induced cytotoxicity compared with ATF3+/+ MEFs. This study identifies cisplatin as a MAPK pathway-dependent inducer of ATF3, whose expression influences cisplatin's cytotoxic effects.